Comparison of Molten Salts and Thermal Oil in Parabolic Trough Power Plants for Different Sites and Different Storage Capacities - Jürgen Dersch; Michael Karl Wittmann; Tobias Hirsch (Energies)
This study compares the levelized cost of energy (LCOE) of parabolic trough solar power plants using thermal oil or two different molten salt mixtures located at three different sites and with different thermal storage capacities. The necessity of using appropriate model approaches for the temperatures along a loop of the solar field is discussed, as well as the utilization of heat from thermal storage for freeze protection of the molten salt plants. The ternary salt mixture with a lower temperature limit of 170 °C and an upper temperature limit of 500 °C shows the lowest LCOE for all sites and almost all investigated storage capacities. Molten salts as heat transfer fluids are particularly favorable for sites with high irradiation and plants with large storage capacities of more than six full load hours.